Interactive Multimedia Using Canva Application in Basic Electronics Subject for Grade X at SMK Negeri 1 Batipuh: A Development Study - Sandi Azima Mailando; Ika Parma Dewi; Hanesman; Agariadne Dwinggo Samala (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
This research is motivated by the low student learning outcomes due to the learning process still relying on printed books, the absence of interactive multimedia learning media, and the use of traditional methods. The main objective of this study is to evaluate the validity and practicality of interactive multimedia using the Canva application in the Basic Electronics subject for the 10th grade at SMK Negeri 1 Batipuh. To carry out this development, the 4D research model is employed, including the Define, Design, Development, and Disseminate steps. The results of material expert validation show an average score of 0.883, categorizing it as "Valid." The average score from the media expert verification is 0.914, also falling into the "valid" category. The practicality test of the Basic Electronics multimedia learning demonstrates that it is highly practical for use in the learning process, with an average percentage of 91%, falling into the "Very Practical" category.